Chapter Видовые приставки в языковом контакте (на материале молизско-славянского, резьянского и верхнелужицкого микроязыков) - Pila, Malinka (Biblioteca di Studi Slavistici, 2017)
This paper deals with Slavic micro-languages in situations of absolute language contact with German (Upper Sorbian, Burgenland Croatian) and Italian (Molise Slavic, Resian). The Slavic way of forming aspectual pairs has been preserved throughout, whereas aspect usage has changed. The behaviour of prefixes in borrowings varies according to the individual contact situations: Sorbian and Burgenland Croatian form prefixed partners even from loan verbs in contrast to Resian and Molise Slavic, borrowing telic verbs as perfectives and forming their imperfective partners by means of suffixation.